Store loyalty, retail satisfaction and competitive resistance towards purchase intention - Ma’rof, Rabiatul Adawiyah; Nik Mat, Nik Kamariah; Rashid, Umi Kartini; Nasuredin, Juzaimi; Sanita, Fitriah (Scientific & Academic Publishing Co., 2012)
This paper explores the factors that influence the consumers’ intentions towards purchasing behaviour.Specifically, the objective of this study is to determine the relationships between retail satisfaction, loyalty to the store and competitive resistance toward purchase intention among the staff of a university in the North of Malaysia. All variables were measured from developed instrument using 7-point interval scale. The exogenous variable are retail satisfactions (8 items), loyalty to the store (9 items) while endogenous variables are competitive resistance (2 items) and purchase intention (2 items).A total of 103 staffs, based on random sampling method selected from various age, gender, education and income, participated in this study.The instrument is validated using exploratory factor analysis (EFA) resulting in three similar components as the exogenous.The data was then analysed using Structural Equation Modeling (SEM). The result shows that the goodness of fit indices of structural equation model are achieved at GFI=0.915, P-value=0.087, RMSEA=0.057 and ratio (cmin/df) =1.316. The finding supports one significant direct effect in the revised model, thus supporting the hypothesis regarding store loyalty is positively related to purchase intention (β=0.961, CR=3.578, p<0.001).The structural model explains 80.7 per cent variance in purchase intention.The result is discussed in the perspective of consumers’ loyalty towards purchase intention.